The Mediating Effect of Brand Trust on The Influence of Communication, Price, and Product Quality on Consumer Purchase Behaviour in a Less-Developed Country (Malaysian Management Journal, 2016)
Brand trust is one of the key elements in brand building and securing customer loyalty, based on relationship marketing factors. The aim of this research was to examine the influence of perceived product price, perceived product quality and communication on brand trust, and the effect of brand trust on consumer purchase behaviour based on the relationship theory perspective. The research instrument was developed based on items taken from previous studies. Questionnaires were distributed to 1400 consumers in 10 primary and secondary schools in three towns in Sanaa, Ibb, and Aden in Yemen. Only 711 questionnaires were used for statistical analysis, using Partial Least Squares (PLS–SEM). Results indicated that trust has a positive significant impact on purchase behaviour. Trust is also a mediator between communication and purchase behaviour, and between perceived quality and purchase behaviour. In addition, this study showed that both perceived product quality and communication positively influence building brand trust. The constructed model has a good goodness-of-fit index. This research also discussed practical implications and applications in developing and less-developed countries.